INTEGRATION OF ISLAMIC VALUES IN THE TRADITION OF TRAMPLING EGGS AT JAVANESE WEDDING CEREMONIES IN BATANG KUIS PEKAN VILLAGE, BATANG KUIS DISTRICT, DELI SERDANG REGENCY - Pradana, Chandra Anggi; Muin, Mohd. Iqbal Abdul (Pena Cendekia Insani, 2026)
Traditions are one form of local wisdom passed down thru generations and still preserved by society, including in the context of Javanese traditional weddings. One tradition that is still maintained is the egg-stepping ceremony, where the groom steps on chicken eggs that are then cleaned by the bride. This process has deep philosophical significance, namely the husband's readiness to take on household responsibilities and the wife's sincerity in supporting and serving her partner. However, the tide of modernization has led some young generations to view it merely as a ceremonial ritual without understanding the values and philosophy it contains. This research aims to describe the implementation of the egg-stepping tradition among Javanese people in Batang Kuis Pekan Village, analyze the symbolic meaning contained within it, and explain the integration of Islamic values into the tradition. The research uses a qualitative approach with a descriptive method. Data was collected thru observation, interviews with traditional leaders, religious figures, the wedding couple, and community members, as well as documentation of the wedding procession. Data analysis was conducted thru reduction, presentation, and drawing conclusions. The research results show that the egg-stepping tradition is still carried out as part of the cultural identity of Javanese society, with symbolic meanings that align with Islamic teachings, such as responsibility, compassion, justice, and respect within the household. This tradition does not contradict Islamic law; in fact, it can be used as a means of cultural proselytization to strengthen Islamic values in community life. Thus, this research affirms the importance of maintaining a balance between preserving local cultural heritage and implementing Islamic values so that traditions remain relevant in the modern era.